2020
DOI: 10.37970/aps.v4i1.61
|View full text |Cite
|
Sign up to set email alerts
|

The cessation of rising employment rates at older ages in Australia, 2000-2019

Abstract: Background  In the first decade of the 21st century, employment at older ages surged in Australia, benefitting the Australian economy. Subsequent to 2010, however, employment rates at older ages ceased rising for older men and the increases were much more moderate for women. Aim  The aim of this paper is to examine these older-age employment trends in more detail, particularly the association between older-age employment trends and the business cycle. Some attention is also given to alternative explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…In the future this work could be developed in a number of ways, including the delineation of scenarios that capture how the shape of the profile of per capita labor income by age in Australia might change in future years. The shape of this profile changed substantially during the 2000s as a result of increases in mature age labor force participation ( 3 , 5 ), although change was much more moderate in the 2010s ( 33 ). The Australian government's 2021 Intergenerational Report includes projections of labor force participation rates that include some change in the age profile of participation rates in the future ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the future this work could be developed in a number of ways, including the delineation of scenarios that capture how the shape of the profile of per capita labor income by age in Australia might change in future years. The shape of this profile changed substantially during the 2000s as a result of increases in mature age labor force participation ( 3 , 5 ), although change was much more moderate in the 2010s ( 33 ). The Australian government's 2021 Intergenerational Report includes projections of labor force participation rates that include some change in the age profile of participation rates in the future ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite all these changes, the rapid increases in labour force participation that applied during the first decade of the twenty-first century slowed considerably in the second decade (Chomik and Khan 2021). Analysing Australian Bureau of Statistics (ABS) Labour Force Survey data, McDonald and Moyle (2020) have shown that the historic increases in labour force participation at older ages were driven by favourable economic conditions, which saw people both re-enter work in mid-life (under age 55) and, in the following decades, delay their retirement with high retention rates. Entry to the labour force at ages 55 and over was very uncommon.…”
Section: Changes In Labour Force Participation Ratesmentioning
confidence: 99%